Study of Prevalence of Premenstrual Dysphoric Disorder in Nursing Students - Falak Rashid Lone; Manmeet Singh (Journal of Psychosexual Health)
Background: Premenstrual dysphoric disorder (PMDD) is a common yet underdiagnosed mental health problem among women of reproductive age group with a significant potential to perturb social, academic, occupational, and interpersonal milieu of suffering women. The aim of this study is to see the Prevalence of PMDD in Nursing Students. Methods: A cross-sectional questionnaire-based study was conducted among the nursing students of the Acharya Shri Chander College of Medical Sciences Nursing School, Jammu and they were screened for the presence of PMDD using the Premenstrual Symptoms Screening Tool. Results: Prevalence of moderate to severe Premenstrual Syndrome (PMS) was 28.1% and PMDD was 6.1%. The commonest premenstrual symptom among the cases was fatigue or lack of energy. In the moderate to severe PMS category, it was anger, and in the PMDD category, it was anxiety. Impairment of college efficiency, or productivity was in 81.3% and 100.0% of students having moderate to severe PMS and PMDD, respectively. Conclusion: PMS and PMDD were prevalent among a substantial proportion of nursing students with significant negative influence on academic performance, emotional well-being and behavior. Strategies should be adopted in college health programs for the timely recognition and management of PMS and PMDD in nursing students.